Physics Teachers’ Competence and Extent of Use of Laboratory Approaches - Remigio, John Marvin F.; Antonio, Vida V.; Calzada, Marc Paul T. (Future Science / FSH-PH Publications, 2025)
Science education is vital for developing students' critical thinking, problem-solving skills, and scientific literacy. Effective scientific training relies on both theoretical instruction and hands-on experience using laboratory equipment. Laboratories serve as essential instructional environments where students explore scientific principles, conduct experiments, and apply theoretical knowledge in practical situations. The efficient utilization of laboratory equipment predominantly depends on the expertise of science educators in administering and integrating these resources into their instruction. Hence, a descriptive-correlational research approach was conducted to determine the knowledge and skill competence of public school teachers in the Schools Division of Ilocos Norte. Using a researcher-made survey questionnaire, it was revealed that the respondents have very high competence when it comes to laboratory instruction. With a positive correlation, the results revealed that teachers with high competence in laboratory techniques, equipment handling, and experiment facilitation are more likely to integrate laboratory activities into their teaching, fostering active learning and scientific inquiry among students. The study emphasizes the importance of continuous professional development and skills training to maximize the use of laboratory resources. Thus, Schools should invest in training programs and provide adequate facilities to ensure teachers can effectively implement laboratory-based instruction, enhancing instructional effectiveness and student engagement in science learning.